Hemophagocytic lymphohistiocytosis resulting from a cytokine storm triggered by septicemia in a child with chronic granuloma disease: a case report and literature review - Ang Wei; Honghao Ma; Liping Zhang; Zhigang Li; Qing Zhang; Dong Wang; Li Zhang; Hongyun Lian; Rui Zhang; Tianyou Wang (BMC Pediatrics, 2020)
Abstract Background Hemophagocytic lymphohistiocytosis (HLH) is a rare potentially fatal illness characterized by impaired natural killer and cytotoxic T cell function. Chronic granulomatous disease (CGD) is an inherited immune deficiency caused by a defect in the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase complex. CGD patients display an increased susceptibility to infection with bacteria and fungi. Repeated infections lead to an increased risk for developing HLH. The case of CGD with repeated Salmonella septicemia complicated with HLH is very rare, and the CGD mutation identified has not been reported. Case presentation A 3-year-old boy was admitted to our hospital for fever, hepatosplenomegaly and pancytopenia. According to the clinical manifestations and laboratory results, hemophagocytic lymphohistiocytosis (HLH) was diagnosed. Blood and bone marrow culture confirmed septicemia due to Salmonella Typhimurium. On the basis of antiinfection treatment, methylprednisolone was used to control HLH. After treatment, the clinical symptoms and laboratory results improved. Gene analysis showed a novel hemizygous CYBB gene mutation: c.302A > G (p.H101P). Combined with a past history of recurrent infection, the child was diagnosed with HLH secondary to CGD triggered by septicemia. Conclusions In case of a known (or highly suspected) CGD with a documented infection, clinical or biological features of HLH should encourage the physician to make possible to confirm or not the HLH. Therefore, to initiate the adequate treatment in association with anti-infective therapy.